Income in Jeopardy: How losing employment affects the willingness to take risks - Clemens Hetschko; Malte Preuss (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2015)
Using German panel data, we assess the causal effect of job loss, and thus of an extensive income shock, on risk attitude. In line with predictions of expected utility reasoning about absolute risk aversion, losing ones job reduces the willingness to take risks. This effect strengthens in previous hourly wage, begins to manifest itself as soon as an employee perceives the threat of job loss and is of a transitory nature. The change in stated risk attitude matches observable job finding behaviour, confirming the behavioural validity of our results.
Keywords: D81; J64; J65; 330; absolute risk aversion; income shock; job loss; plant closure; general risk attitude